Evaluation of the Quality of Antibiotic Prescribing in Primary Care: A Multicenter Longitudinal Study From Shenzhen, China - Gong, Yanhong; Li, Hui; Yang, Heping; Tan, Kun; Liu, Wei; Li, Xiaotong; Wu, Jianxiong; Zhang, Guopeng; Yin, Xiaoxv (Frontiers in Pharmacology, 2021)
Abstract Background: Currently, there is no comprehensive evaluation of the quality of antibiotic prescribing in China’s primary care facilities based on longitudinal data. Methods: We randomly selected 11 community health centers in Shenzhen, China, and collected all outpatient prescriptions of these centers from 2010–2015. To evaluate the quality of antibiotic prescribing, we used six quality indicators for analysis, including number of antibiotics per 100 consultations, ratio between broad-spectrum and narrow-spectrum antibiotics (B/N ratio), percentage of first-line antibiotics recommended by guidelines, percentage of oral antibiotics with a duration exceeding the guideline recommendation, and new pediatric-specific indicators such as percentage of antibiotics with amoxicillin (A index) and ratio between amoxicillin and broad-spectrum antibiotics (A/B ratio). Results: During the study period, 571 362 outpatient consultations resulted in antibiotic prescriptions, which contained 706 411 antibiotics. The overall number of antibiotics per 100 consultations decreased significantly from 93.50 in 2010 to 19.98 in 2015 (P=0.004), but the B/N ratio showed an upward trend over time (P=0.009). In different populations and different common infections, the number of antibiotics used decreased to varying degrees, while the B/N ratio increased to varying degrees, with the most obvious change in children <5 years. The percentage of first-line antibiotics for common infections was not high, ranging from 3.45% to 44.25% during 2014-2015. The percentage of oral antibiotics with an exceeded duration ranged from 0.70% to 19.39%. Moreover, the A index and A/B ratio in children remained low for a long time, which was 0.76% and 0.01 in 2015. Conclusions: A review of antibiotic prescribing in Shenzhen, China, showed a substantial reduction in antibiotic use in primary care. However, problems such as widespread use of broad-spectrum antibiotics, insufficient use of first-line antibiotics and low use of amoxicillin were prevalent. Improving and optimizing the quality of antibiotic prescribing, particularly in children prescriptions, will be the focus of future antibiotic stewardship in China.